Development of a SYBR green based real-time polymerase chain reaction assay for specific detection and quantification of Vibrio parahaemolyticus from food and environmental samples. - V, Micky; AT Nur, Quraitu; L, Velnetti; RMB, Patricia; C, Christy; MB, Lesley (Faculty of Food Science and Technology, 2014)
Vibrio parahaemolyticus is a foodborne pathogen and their human infection is regularly associated with the consumption of raw or undercooked seafood and contaminated water supplies. Many conventional biochemical identification and confirmation procedures are performed to detect the presence of this pathogen, both from seafood or environmental samples. However, these procedures not only require two or more days to complete, they do not have the capabilities to determine the number of V. parahaemolyticus cells in any given samples. Thus, in this study we describe the development of a rapid SYBR green based real-time PCR assay, targeting the thermo labile (tl) gene of V. parahaemolyticus for the detection and enumeration of this bacterium from seafood and environmental samples. We report that the real-time PCR assay and the primers designed are highly specific, and only generated the desired amplicons with V. parahaemolyticus DNA samples against other bacteria and fungi species. Our assay is also highly sensitive, and, is able to detect V. parahaemolyticus with high coefficient values in concentrations as low as 1.0 pg/μl DNA for pure genomic DNA solutions and 10 cells/ml in serially diluted cell suspension and spiked samples. This assay can be completed in less than 3 hours and may be used as a tool for rapid determination of V. parahaemolyticus densities in the food industries, environmental risk assessment and for clinical diagnostics purposes.